The Review of the Situation on Anthrax in 2024 in the World, the Forecast for 2025 in the Russian Federation - A. G. Ryazanova; D. K. Gerasimenko; T. M. Golovinskaya; O. N. Skudareva; F. V. Logvin; O. V. Semenova; L. Yu. Aksenova; E. I. Eremenko; G. A. Pechkovsky; K. A. Oleynikova; A. V. Nikitina; A. N. Kulichenko (Проблемы особо опасных инфекций)
Epizootiological and epidemiological situation on anthrax in the world in 2024 has been reviewed, dynamics of anthrax incidence in the period of 2015–2024 and the forecast of anthrax incidence in 2025 in the Russian Federation are presented. In 2024, one outbreak of anthrax was detected in Russia, in a constituent entity of the Central Federal District, with the disease affecting two farm animals and three people. Compared to 2023, when seven outbreaks were registered in five regions, in 2024 Russia saw a decrease in the number of infection cases by 12 – among farm animals and 16 – among people. Anthrax manifested in four neighboring countries, with the most unfavorable situation occurring in Kazakhstan and Kyrgyzstan. Outbreaks of infection among farm and wild animals were recorded on all continents, with the largest number of cases in Africa and Asia. Cases of anthrax in humans have been identified in a number of countries in Africa, Asia, North and South America and Europe and were caused by contact with sick farm animals during forced slaughter, butchering of carcasses and meat, and eating meat from sick and dead animals. Also, in one of the Asian countries (Pakistan), a bioterrorism act was implemented through distributing letters containing anthrax spores, which did not lead to human infection. The incidence of anthrax in animals and humans in 2025 in the Russian Federation will depend on the scale of animal registration and vaccination measures, the completeness of inclusion of population at risk in immunization scheme and implementation of preventive vaccination plans. With strict adherence to anti-anthrax monitoring and surveillance measures, the incidence of anthrax in Russia will not exceed the level of isolated cases.